Solve:

2y-a = a + 3b
____ ______, for y
3 4

Please show how to solve this.

If you mean
(2y -a)/3 = (a + 3b)/4
then
2y - a = (3/4) (a + 3 b)
2y = (7/4) a + (9/4) b
y = (7/8) a + (9/8) b

f(x)=x(squared)-4x+9

solve for x

## To solve the equation f(x) = x^2 - 4x + 9, we want to find the values of x that make the expression equal to zero. This means we are solving for the x-intercepts or roots of the equation.

To solve this quadratic equation, you can use either the factoring method, completing the square method, or the quadratic formula. Let's solve it using the quadratic formula.

The quadratic formula is given by:

x = (-b ± √(b^2 - 4ac)) / (2a)

In our equation, a = 1, b = -4, and c = 9. Substituting these values into the formula, we get:

x = (-(-4) ± √((-4)^2 - 4(1)(9))) / (2(1))
x = (4 ± √(16 - 36)) / 2
x = (4 ± √(-20)) / 2

Since the square root of a negative number is not a real number, we can conclude that the equation has no real roots. Therefore, there are no values of x that solve the equation f(x) = x^2 - 4x + 9.